2017
DOI: 10.1021/acs.inorgchem.7b01247
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium and Technetium-oxo Complexes with Thioamide Derivatives of Pyridylhydrazine Bifunctional Chelators Conjugated to the Tumour Targeting Peptides Octreotate and Cyclic-RGDfK

Abstract: This research aimed to develop new tumor targeted theranostic agents taking advantage of the similarities in coordination chemistry between technetium and rhenium. A γ-emitting radioactive isotope of technetium is commonly used in diagnostic imaging, and there are two β– emitting radioactive isotopes of rhenium that have the potential to be of use in radiotherapy. Variants of the 6-hydrazinonicotinamide (HYNIC) bifunctional ligands have been prepared by appending thioamide functional groups to 6-hydrazinonicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…To better understand the potential e cacy of the selected Rhenium compound in a tumour setting, we tested the effect of JVG045 on primary cell cultures derived from pancreatic ductal adenocarcinoma isolated from KrasLSL.G12D/+; p53R172H/+; PdxCretg/+ (or KPC) mice. We found that JVG045 impairs KPC primary cell growth in a dose-dependent manner (Fig 3A,B), reaching statistical signi cance at 5 and 10μM (One-way ANOVA F (4,20) =11.87, p<0.0001). We also tested the effect of 10mM JVG045 on anchorage independent soft agar colony formation, which measures the ability of cancer cells to grow and to proliferate without support on a solid surface (29,43).…”
Section: Resultsmentioning
confidence: 81%
“…To better understand the potential e cacy of the selected Rhenium compound in a tumour setting, we tested the effect of JVG045 on primary cell cultures derived from pancreatic ductal adenocarcinoma isolated from KrasLSL.G12D/+; p53R172H/+; PdxCretg/+ (or KPC) mice. We found that JVG045 impairs KPC primary cell growth in a dose-dependent manner (Fig 3A,B), reaching statistical signi cance at 5 and 10μM (One-way ANOVA F (4,20) =11.87, p<0.0001). We also tested the effect of 10mM JVG045 on anchorage independent soft agar colony formation, which measures the ability of cancer cells to grow and to proliferate without support on a solid surface (29,43).…”
Section: Resultsmentioning
confidence: 81%
“…Enlarging this finding to the corresponding nicotinylthiosemicarbazide ligand offered an additional free carboxylic group available to append targeting molecule. Such a strategy has been used to tether the Re(V) to Tyr3-octreotate and cyclic-RGD tumor targeting peptides [32]. Many heterobimetallic compounds have been synthesized…”
Section: Chemical Structuresmentioning
confidence: 99%
“…Re in this form (Figure 6) [69]. proven itself as a versatile radiolabelling synthon for coupling to a range of chelators conjugated to targeting molecules, and for direct labelling of proteins (Figure 7).…”
Section: Stable Well-defined Chelated Derivative With the Square Pyrmentioning
confidence: 99%